Dimensions of the KidCope and their associations with mental health outcomes in Tanzanian adolescent orphans - Megan Cherewick; Samantha Bertomen; Prosper F. Njau; Jenn A. Leiferman; Ronald E. Dahl (Health Psychology and Behavioral Medicine, 2024)
Background Adverse life experiences require a broader range of adaptive behavioral strategies to cope with related stressors. The association between intensity, duration, type of stress and impacts on mental health is important for effective programming aimed at increasing resilience in the face of stress. This study examines adverse life experiences, coping strategies, and associations with mental health outcomes among very young adolescent orphans.Methods The analytic sample was collected between January and March of 2019 and included 350 adolescent orphans ages 10–15 years old from three districts in Tanzania. Participants completed survey interviews, 75–90 minutes in length, that measured adverse life experiences, stigma, coping strategies, and psychological symptoms.Results A four-factor dimensional structure of the KidCope survey fits these data and distinguished between distraction and resignation coping strategies. Use of distraction as a coping dimension was the most frequently used coping dimension and was associated with lower reported symptoms of depression, anxiety, and externalizing behaviors. Resignation was positively associated with adverse life experiences including emotional abuse, emotional neglect, and physical neglect. Problem-focused coping was not associated with study outcomes and social support coping was associated with externalizing behaviors only.Conclusion Results from adolescent orphans in a low-resource context suggest that distraction coping strategies may be adaptive in response to stress. Implications for intervention programming that aims to target acquisition of coping skills and mindsets among vulnerable populations are discussed.